The role of cytoskeleton in the regulation of contractile activity in smooth muscle cells from aorta of rats - S. V. Gousakova (Бюллетень сибирской медицины)
Influence of cytoskeleton modulation by Colchicine and Cytochalasine B on contractile reactions of smooth muscle segments of rat's aorta caused by physiologically active substances, the membrane's depolarization and cells' striction was investigated by mechanographical method. Microtubules and actinic elements of the cytoskeleton were established to participate in the development of hyper-potassic and phenylephrine -induced contractions as well as in the smooth muscle relaxation induced by cAMP. Cytochalasine B suppresses both kinds of aortic smooth muscle contractions more effectively than Colchicine. Contractile reactions at isoosmotic striction are suppressed only by Cytochalasine. Efficacy of cAMP signal system operating depends on actinic cyto-skeleton integrity.